2013
DOI: 10.1007/s00508-013-0321-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Lichtenstein tension-free mesh hernia repair on testicular arterial perfusion and sexual functions

Abstract: Lichtenstein tension-free mesh hernia repair does not have any negative effects on testicular perfusion and sexual function; it can be performed safely for treatment of inguinal hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…The control group included the patients who underwent inguinal hernia repair since both procedures were similar in terms of surgical approach, operation time, anesthesia, postoperative followup, and possible surgical stress. In a previous study, Bulus, Dogan, Tas, Agladıoglu, and Coskun (2013) concluded that tension-free mesh hernia repair does not have any negative effect on testicular perfusion and sexual function and can be safely performed for the treatment of inguinal hernia (Bulus et al, 2013). To the best of our knowledge, this is the first study investigating the possible role of varicocelectomy procedure on the postoperative increase in NSE frequency and libido.…”
Section: Discussionmentioning
confidence: 78%
“…The control group included the patients who underwent inguinal hernia repair since both procedures were similar in terms of surgical approach, operation time, anesthesia, postoperative followup, and possible surgical stress. In a previous study, Bulus, Dogan, Tas, Agladıoglu, and Coskun (2013) concluded that tension-free mesh hernia repair does not have any negative effect on testicular perfusion and sexual function and can be safely performed for the treatment of inguinal hernia (Bulus et al, 2013). To the best of our knowledge, this is the first study investigating the possible role of varicocelectomy procedure on the postoperative increase in NSE frequency and libido.…”
Section: Discussionmentioning
confidence: 78%
“…Bulus et al investigated the effects of perimesh fibrosis and edema on testicular arterial flow and sexual function following Lichtenstein tension-free mesh repair. They found that hernia repair did not have any negative effects on sexual activity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bulus et al 18 found no adverse effects on testicular perfusion at the Doppler in patients submitted to hernia repair by the Lichtenstein technique. They found, however, a statistically significant increase in mean arterial flow velocity on the side of the hernia after surgery, and this change was considered transient.…”
Section: ■ Discussionmentioning
confidence: 99%